Assessment on effect of geometry defect for steel pipe - Rabbiatul Addawiyyah, Ahmad Bustaman (2013)
The aim of this research is to study the effect of geometry defects for steel pipe subjected to stress-based criteria. The objectives for this project are to simulate the effect of corrosion geometry on steel pipeline with variable defect depth and to determine the maximum pressure on different defect geometry. This study focused on effect of width and depth defect for rectangular and groove defect. The scope of research consists of material made of API 5L grade B which involve of elastic and plastic deformation. The MSC Marc 2008r1 is used to simulate 2-D corrosion defect of pipeline which involved groove defect and rectangular defect with variables in depth and width defect. There are three different widths (0.2mm, 0.5mm and 1mm) and depths (20%, 50% and 75% from the wall thickness) are selected to be analysed. The simulation involved about 18 designs of defects. Meanwhile, half of the pipe model with the outer diameter of 60.5mm and wall thickness 4mm were simulated to analyse the defect condition. The FEA result will be compared in terms of depth defect and length of width. Besides, it also will be compared with the industry codes such as ASME B31G, Modified ASME and DNV-RP-F101. Based on analysis, the width of defect does not affect much upon the burst pressure. However, depth of corrosion defect plays an important role for the pipeline to be failed in operation. The deep defect is easily reach burst pressure compare to the shallow defect and moderately defect. On the top of that, the FEA result for burst pressure is much higher rather than industry codes. From the analysis done, the groove defect and rectangular defect tends to failed at almost the same burst pressure even the width is different. In a nutshell, the depth of corrosion defect plays an important role for burst pressure rather than width. Moreover, the different type of defect does not give huge impact on the burst pressure